2005
DOI: 10.1556/abiol.56.2005.3-4.14
|View full text |Cite
|
Sign up to set email alerts
|

The cytogenetic effects of avenoxan onAllium cepaand its relation with pollen sterility

Abstract: In the present study, the cytogenetic effects of the herbicide Avenoxan on meiotic chromosomes of Allium cepa and its relation with pollen sterility were studied. The bulbs with roots of Allium cepa were treated with a series of concentrations (0.1%, 0.2%, 0.4%) for 3, 6, 12 and 24 h. Controls and treated plants were shown to obtain M1 generation. All the used concentrations of the herbicide Avenoxan and exposure periods caused distinct increase in the number of abnormal cells when compared with the control. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Similar observations have been reported by Jabee et al (2008) and Kaymak and Gokalp (2005) in Allium cepa, Pline et al (2003) in cotton, and by Thomas et al (2004) in corn. Variation in size of pollen was also observed.…”
Section: Or Zea Mays (Grant and Owens 2006) Highersupporting
confidence: 91%
“…Similar observations have been reported by Jabee et al (2008) and Kaymak and Gokalp (2005) in Allium cepa, Pline et al (2003) in cotton, and by Thomas et al (2004) in corn. Variation in size of pollen was also observed.…”
Section: Or Zea Mays (Grant and Owens 2006) Highersupporting
confidence: 91%
“…The effect of these substances can be attributed to their effect that kill gametes (preventing microsporogenesis and stopping the opening of anthers without affecting female fertility), and when they applied with certain doses at the stage of anthers development, they prevent fertile pollen development and gives deformed pollen that is incapable of growth or fertility (Cross and Ladyman, 1991). Previous findings are consistent with those of Chauhan and Singh (2002), Singh and Chauhan (2003), Kaymak and Gökalp Muranli (2005), Badino (1981), Khatib et al, (2016), andSingh et al, (2018). Agnihotri et al, (2007) showed that GA 3, the herbicide Dichlorophenoxy acetic acid 2,4-D, and washing powder at high concentrations caused sterility in pollen on different plants.…”
Section: Discussionsupporting
confidence: 60%
“…Agnihotri et al, (2007) demonstrated that when spraying radish flowers with three concentrations of washing powder for several times, the lowest concentration of 0.5% with 3 spraying times gave 100% sterile pollen grains with the least decrease in productivity. Kaymak and Gökalp Muranli (2005) concluded that when soaking onion roots in 0.1, 0.2, 0.3, and 0.4% of Avenoxan (the commercial compound of the herbicide 2,4-D) and for several periods (6-12-24 hours), the chromosomal abnormalities increased with the increment of concentration and duration of treatment, and consequently the proportion of sterile pollen grains increased. Tripathi and Singh (2008) showed that washing powder succeeded in producing male sterility in several plant species when treated with low concentrations, while high concentrations caused a great abnormality.…”
Section: Introductionmentioning
confidence: 99%